(untitled) (Scientific journal of the Fergana State University, 2023)
This article analyzes the relations between the Russian Empire and Afghanistan in the second half of the 19th-early 20th centuries, the military-political competition of the two countries in Central Asia, its results, the participation of the Turkestan military in this process was analyzed by the administration.